Buddhism and decision making at individual, group and organizational levels. Issue 8 (2nd September 2014) - Vallabh, Priyanka; Singhal, Manish
Abstract : Purpose: – The purpose of this paper is to explore how practical wisdom rooted in Buddhism can help modern managers make decisions in contemporary business organizations. Design/methodology/approach: – The paper suggests a model explaining how individual level Buddhist beliefs in Dependent Origination are reflected in behavior of individual through mindfulness, compassion and expansion of self. The model also explores the consequences of above mentioned behavior in terms of individual, group and organizational level decision making, respectively. Findings: – The paper develops propositions which demonstrate the possibility of applying the practical wisdom of Buddhism into the individual, group and organizational decision-making processes. The paper proposes an integrative model and suggests initiatives that can be taken in business organizations and business schools for applying the practical wisdom gleaned from the Buddhist traditions. Research limitations/implications: – The paper brought the core concepts of Buddhism as the main point of application in the decision-making process in management. However, this approach is perhaps difficult to grasp for the readers who may not be as conversant with that tradition. Originality/value: – Rich eastern traditions have remained underexplored in contemporary business literature. This paper examines the potential contributions from the Buddhist heritage in the crucial decision-making domain in management.